Leveraging Audiovisual Psycholinguistic Interventions to Enhance Sports Facility Income: Evidence from Systematic Review and Meta-Analysis - Putri Dewanti, Pramusinta; Sumaryanti, Sumaryanti; Sigit Nugroho; Fadli Ihsan; Bekir Erhan Orhan (International Journal of Sport Studies for Health, 2026)
Objective: This study systematically reviews and synthesises research on the effectiveness of audiovisual psycholinguistic interventions in enhancing consumer behaviour and financial outcomes in sports facilities. Methods: A systematic review and meta-analysis were conducted following PRISMA guidelines. Studies published between 2020 and 2025 were retrieved from Scopus, Web of Science, PubMed, and Google Scholar. Eligible studies integrated linguistic and audiovisual elements with measurable outcomes related to engagement, satisfaction, loyalty, willingness-to-pay, and revenue. Effect sizes were calculated alongside tests for heterogeneity and publication bias. Results: The findings show that audiovisual psycholinguistic interventions significantly improve consumer and economic outcomes. The strongest effects were observed for willingness-to-pay (g = 0.71), engagement (g = 0.65), and satisfaction (g = 0.62), with additional benefits for loyalty (g = 0.57) and retention (g = 0.54). Heterogeneity was low to moderate, and no significant publication bias was detected, confirming the robustness of the results. Conclusion: Audiovisual psycholinguistic interventions are effective strategic tools for both enhancing consumer engagement and supporting the financial sustainability of sports facilities. Facility managers are encouraged to integrate motivational narratives, positive linguistic framing, and immersive audiovisual technologies to strengthen customer experience and long-term revenue growth. Future research should extend cross-cultural analyses and employ longitudinal designs to evaluate lasting economic effects.